A new and highly sensitive resonance Rayleigh scattering assay for lysozyme using aptamer–nanogold as a probe. (10th April 2014) - Ma, Lu; Zhang, Xinghui; Liang, Aihui; Liu, Qingye; Jiang, Zhiliang
ABSTRACT Gold nanoparticles (GN), 10 nm in size, were modified by using lysozyme aptamer (Apt) to obtain a stable Apt–GN probe in pH 8.05 Tris/HCl buffer solutions containing 0.04 mol/L NaCl. Upon addition of lysozyme (LYS), it reacted with the Apt of the probe to form a very stable Apt–LYS complex and to release GNs, which aggregated to form large clusters with a resonance Rayleigh scattering (RRS) peak at 368 nm. The enhanced peak intensity, ΔI, was linear to the LYS concentration in the range 0.2–5.2 nmol/L, with a detection limit of 0.05 nmol/L. The influence of foreign substance was tested, and the results showed that this RRS method has high selectivity. This Apt–GN RRS method was applied to the analysis of LYS in a real sample, with satisfactory results. Copyright © 2014 John Wiley & Sons, Ltd.